2012
DOI: 10.1111/j.1749-6632.2012.06641.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasmalogens on systemic lipopolysaccharide‐induced glial activation and β‐amyloid accumulation in adult mice

Abstract: Neuroinflammation essentially involves an activation of glial cells as the cause/effect of neurodegenerative diseases such as Alzheimer's disease (AD). Plasmalogens (Pls) are glycerophospholipids constituting cellular membranes and play significant roles in membrane fluidity and cellular processes like vesicular fusion and signal transduction. Intraperitoneal (i.p.) injection of lipopolysaccharide (LPS, 250 μg/kg) for 7 days resulted in the morphological changes and increase in number of Iba-1(+) microglia sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 52 publications
0
42
0
2
Order By: Relevance
“…Moreover, innate immune-mediated neuroinflammation also occurs in company with Aβ accumulation in AD, which often leads to abundant inflammatory cells, including glial activation that expresses high levels of glucose transporters and thus increases brain glycolytic activity [23,24,25]. Our study revealed the entorhinal cortex and hippocampus as regions affected first with glucose disorders, perhaps because these regions are highly dependent on the insulin signaling pathway and are initially subject to Aβ accumulation [26,27]. While accumulated Aβ causes glucose metabolic disorder by disturbing the insulin signaling pathway, altered glucose metabolism can conversely promote Aβ accumulation.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, innate immune-mediated neuroinflammation also occurs in company with Aβ accumulation in AD, which often leads to abundant inflammatory cells, including glial activation that expresses high levels of glucose transporters and thus increases brain glycolytic activity [23,24,25]. Our study revealed the entorhinal cortex and hippocampus as regions affected first with glucose disorders, perhaps because these regions are highly dependent on the insulin signaling pathway and are initially subject to Aβ accumulation [26,27]. While accumulated Aβ causes glucose metabolic disorder by disturbing the insulin signaling pathway, altered glucose metabolism can conversely promote Aβ accumulation.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is not clear whether the decrease of Pls in brain tissue and in plasma is the cause of the disease or merely a result of the disease. Recent studies of animal models of AD by our group indicated that intraperitoneal administration of purified Pls improved cognitive function (Katafuchi et al, 2012, Hossain et al, 2013, Hossain et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Plasmalogens (Pls) constitute a special class of glycerophospholipids characterized by the presence of a vinyl ether linkage at the sn-1 position of the glycerol backbone [1-4]. Pls are found in various human tissues including their major presence in the nervous, cardiovascular and immune systems [1,4].…”
Section: Introductionmentioning
confidence: 99%